2022
DOI: 10.3389/fmicb.2022.1035941
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota analysis and network pharmacology reveal the mechanism by which Lianhua Qingwen capsule improves the immune function of mice infected with influenza A virus

Abstract: ObjectiveLianhua Qingwen capsule (LHQW) can attenuate lung injury caused by influenza virus infection. However, it is unclear whether the intestinal microbiota plays a role in LHQW activity in ameliorating viral infectious pneumonia. This study aimed to investigate the role of intestinal microbiota in LHQW activity in ameliorating viral infectious pneumonia and its possible mechanisms.Research design and methodsA mouse model of influenza A viral pneumonia was established by intranasal administration in BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 79 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…LHQW can be used to treat COVID-19 by targeting ACE2 and 3CL pro , achieving immunoregulation via targeting the immune responses to SARS-CoV-2, providing anti-inflammation activity by targeting cytokines, and thus demonstrating anti-viral potency against SARS-CoV-2 [73] . The results of intestinal microbiota analysis and network pharmacology have revealed that LHQW can be used to effectively treat influenza A virus–infected pneumonia, the mechanism of which may be related to the regulation of the lung TLR4/NF-κB signaling pathway by restoring intestinal flora and repairing the intestinal wall [74] .…”
Section: Potential Mechanisms Through Which Tmtfs Treat Covid-19mentioning
confidence: 99%
“…LHQW can be used to treat COVID-19 by targeting ACE2 and 3CL pro , achieving immunoregulation via targeting the immune responses to SARS-CoV-2, providing anti-inflammation activity by targeting cytokines, and thus demonstrating anti-viral potency against SARS-CoV-2 [73] . The results of intestinal microbiota analysis and network pharmacology have revealed that LHQW can be used to effectively treat influenza A virus–infected pneumonia, the mechanism of which may be related to the regulation of the lung TLR4/NF-κB signaling pathway by restoring intestinal flora and repairing the intestinal wall [74] .…”
Section: Potential Mechanisms Through Which Tmtfs Treat Covid-19mentioning
confidence: 99%